Down-regulation of miR-144 after Mycobacterium tuberculosis infection promotes inflammatory factor secretion from macrophages through the Tpl2/ERK pathway - Liu, H-Y (Cellular and Molecular Biology, 2016)
Pulmonary tuberculosis is one of the deadliest human diseases and mainly occurs when the immune system is impaired. MicroRNAs (miRNAs) have a critical role in regulating innate and adaptive immunity. Based on previous reports that Mycobacterium tuberculosis (M.tb) can modulate host cell miRNA expression, this study aimed to investigate expression changes in miR-144 and miR-144 regulate macrophage function via targeting of tumor progression locus 2 (Tpl2, also named MAP3K8) and extracellular signal-regulated kinase (ERK) signaling. I examined the miRNA expression profile of M.tb–infected monocyte-derived macrophages (MDMs) by gene expression profiling and quantitative real-time PCR (qRT-PCR). miR-144 is obviously down-regulated in MDMs infected with M.tb and directly binds to the 3'-UTR of Tpl2, acting as a negative regulator. Moreover, inhibiting miR-144 or over-expression of Tpl2 can activate the ERK signaling pathway by inducing ERK1/2 phosphorylation. At the same time, TNF-Î±, IL-1Î² and IL-6 secretion were significantly accelerated. Taken together, these results suggest that miR-144 is expressed at a low level in M.tb–infected MDMs and acts as a negative regulator for Tpl2 target, which is closely connected with ERK signaling that regulates inflammatory factor secretion.